Analysis of Social Values and Characteristics in the Short Story Tupai Si Never Give Up Written SDN 13 Kolo Kota Bima - Khairani, Ita; Khairina, Isni; Wulan, Eka Putri Saptari (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
This study aims to examine the social values and characteristics contained in the short story 'Tupai Si Pantang Surrender' written by SDN 13 KOLO BIMA. The theory used is the theory of humanism put forward by Abraham Maslow with a sociology of literature approach. The method used in this research is a descriptive method with a qualitative research form. The subject of this research is the short story Tupai Si Unyielding' which was written by SDN 13 KOLO BIMA. The research data is in the form of paragraph excerpts and sentence fragments that contain elements of social values. The results of the study show that the social values contained are, 1) unyielding attitude, 2) compassion, 3) respect not demeaning, 4) persistence and hard work produce results according to what we use, 5) struggle, 6) admiration, 7) Regret. This study delves into the analysis of social values and characteristics embedded in the short story titled "Tupai Si Never Give Up," authored by SDN 13 Kolo Kota Bima. The research aims to uncover the narrative's underlying themes, socio-cultural reflections, and character dynamics. Employing a qualitative approach, the analysis focuses on the portrayal of social values such as perseverance, resilience, and community bonds, as well as the depiction of various characteristics exhibited by the story's protagonists. Through a close examination of the narrative elements, the study seeks to contribute to a deeper understanding of the cultural and social nuances presented in the short story, shedding light on the author's intent and the broader societal context in which the narrative unfolds.